Excess mortality associated with eating disorders: population-based cohort study. (September 2021) - Iwajomo, Tomisin; Bondy, Susan J.; de Oliveira, Claire; Colton, Patricia; Trottier, Kathryn; Kurdyak, Paul
Abstract : Background: Individuals with eating disorders have a high mortality risk. Few population-based studies have estimated this risk in eating disorders other than anorexia nervosa. Aims: To investigate all-cause mortality in a population-based cohort of individuals who received hospital-based care for an eating disorder (anorexia nervosa, bulimia nervosa or eating disorder not otherwise specified) in Ontario, Canada. Method: We conducted a retrospective cohort study of 19 041 individuals with an eating disorder from 1 January 1990 to 31 December 2013 using administrative healthcare data. The outcome of interest was death. Excess mortality was assessed using standardised mortality ratios (SMRs) and potential years of life lost (PYLL). Cox proportional hazards regression models were used to examine sociodemographic and medical comorbidities associated with greater mortality risk. Results: The cohort had 17 108 females (89.9%) and 1933 males (10.1%). The all-cause mortality for the entire cohort was five times higher than expected compared with the Ontario population (SMR = 5.06; 95% CI 4.82–5.30). SMRs were higher for males (SMR = 7.24; 95% CI 6.58–7.96) relative to females (SMR = 4.59; 95% CI 4.34–4.85) overall, and in all age groups in the cohort. For both genders, the cohort PYLL was more than six times higher than the expected PYLL in the Ontario population. Conclusions: Patients with eating disorders diagnosed in hospital settings experience five to seven times higher mortality rates compared with the overall population. There is an urgent need to understand the mortality risk factors to improve health outcomes among individuals with eating disorders.